The Flip Side of Distractibility—Executive Dysfunction in Functional Movement Disorders - Huys, Anne-Catherine M. L.; Bhatia, Kailash P.; Edwards, Mark J.; Haggard, Patrick (Frontiers in Neurology, 2020)
Attention plays a crucial role in functional neurological disorders. Attention to the symptoms leads to their exacerbation and distraction to their improvement or even transitory disappearance. Objective: The aim was to test if the alerting, orienting and particularly the executive aspect of attention are affected in functional movement disorders. Methods: Thirty patients with a functional movement disorder, 30 patients with an organic movement disorder and 30 healthy controls performed the attention network test. Results: The alerting and orienting effects were normal, but executive control of attention under conflict was abnormal in patients with functional movement disorders, compared to patients with an organic movement disorder and healthy controls. Conclusion: Executive dysfunction seems to be an important secondary feature of functional movement disorders, due to the overutilization of attentional resources for explicit movement control. Furthermore, it provides an explanation for seemingly unrelated symptoms commonly associated with functional movement disorders, such as concentration difficulties and fatigue.